Part-Time Workers as Missing Persons in Organizational Research - Rotchford, Nancy L.; Roberts, Karlene H. (Academy of Management Review, 1982)
Although a substantial and growing percentage of the United States labor force, part-time workers have been neglected in organizational research and viewed narrowly in popular and economic literature. Part- and full-time employees appear to differ in at least four important respects, and these relevant variables should be included in comparative studies of these workers. Methodological and policy problems are discussed.